A bioinformatics approach to design a novel epitope-based vaccine against Simian Immunodeficiency Virus (Retroviridae: Lentivirus) - Dhea Kharisma, Viol; Ansori, Arif Nur Muhammad; Ullah, Md. Emdad; Dings, Tim Godefridus Antonius; Probojati, Rasyadan Taufiq; Fadholly, Amaq; Turista, Dora Dayu Rahma; Tacharina, Martia Rani; Zainul, Rahadian (Generasi Biologi Indonesia, 2022)
Simian Immunodeficiency Viruses (SIV) have been found to naturally infect African nonhuman primates (NHP). This causative agents are important and one of the special interest as the root cause of the HIV/AIDS pandemic, one of the most threatening infectious diseases worldwide. The aim of this study was to design an epitope-based vaccine using bioinformatics approaches of the circulating SIV in Kenya, Africa. In this study, we used 17 partial SIV envelope glycoprotein genes retrieved from GenBank® (National Center for Biotechnology Information, USA). We analysed the candidate epitopes using the Immune Epitope Database and Analysis Resource. Then, we performed the protective antigens prediction usingVaxiJen. Interestingly, this study revealed the data of B cell epitope prediction, protective antigens prediction, and molecular phylogenetic of circulating SIV in Kenya, Africa. In sum, this study can be used to design a novel epitope-based vaccine against SIV. We suggest further studies to conduct confirmatory experiments (in vitro and in vivo).